Can obligate apomixis and more stable reproductive assurance explain the distributional successes of asexual triploids in Hieracium alpinum (Asteraceae)?. (11th December 2018) - Mráz, P.; Zdvořák, P.; Hartmann, M.; Štefánek, M.; Chrtek, J.
Abstract: Although reproductive assurance has been suggested to be one of the most important factors shaping the differential distributional patterns between sexuals and asexuals (geographic parthenogenesis), it has only rarely been studied in natural populations of vascular plants with autonomous apomixis. Moreover, there are almost no data concerning the putative relationship between the level of apomictic versus sexual plant reproduction on one hand, and reproductive assurance on the other. We assessed the level of sexual versus apomictic reproduction in diploid and triploid plants of Hieracium alpinum across its distributional range using flow cytometric analyses of seeds, and compared the level of potential and realized seed set, i.e . reproductive assurance, between the two cytotypes under field and greenhouse conditions. Flow cytometric screening of embryos and endosperms of more than 4, 100 seeds showed that diploids produced solely diploid progeny sexually, while triploids produced triploid progeny by obligate apomixis. Potential fruit set was much the same in diploids and triploids from the field and the greenhouse experiment. While in the pollination‐limited environment in the greenhouse apomictic triploids had considerably higher realized fruit set than sexual diploids, there was no significant difference between cytotypes under natural conditions. In addition, sexuals varied to a significantly larger extent in realized fruit set than asexuals under both natural and greenhouse conditions. Our results indicate that triploid plants reproduce by obligate apomixis, assuring more stable and predictable fruit reproduction when compared to sexual diploids. This advantage could provide apomictic triploids with a superior colonisation ability, mirrored in a strong geographic parthenogenesis pattern observed in this species.